Schedule and Program (Symphony in the Flint Hills, 2010)
The schedule of activities, program notes and information about the Kansas City Symphony, Guest Artist Lyle Lovett, Conductor Steven Jarvi, and others.
Keywords: Program notes; Prairie; Lyle Lovett; Steven Jarvi; Kansas City Symphony